Selective Adsorption of Amino Acids in Crystals of Monohydrocalcite Induced by the Facultative Anaerobic Enterobacter ludwigii SYB1 - Zhao, Yanyang; Han, Zuozhen; Yan, Huaxiao; Zhao, Hui; Tucker, Maurice E.; Gao, Xiao; Guo, Na; Meng, Ruirui; Owusu, Daniel Cosmos (Frontiers in Microbiology, 2021)
The morphology, crystal structure, and elemental composition of biominerals are commonly different from chemically-synthesized minerals, but the reasons for these are not fully understood. A facultative anaerobic bacterium, Enterobacter ludwigii SYB1, is used in experiments to document the hydro-chemistry, mineral crystallization, and cell surface characteristics of biomineralization. It was found that carbonate anhydrase and ammonia production were major factors influencing the alkalinity and saturation of the closed biosystem. X-ray diffraction (XRD) spectra showed that calcite, monohydrocalcite (MHC), and dypingite formed in samples with bacterial cells. It was also found that the (222) plane of MHC was the preferred orientation compared to standard data. Scanning Transmission Electron Microscopy (STEM) analysis of cell slices provides direct evidence of concentrated calcium and magnesium ions on the surface of extracellular polymeric substances (EPS). In addition, high-resolution transmission electron microscopy (HRTEM) showed that crystallized nanoparticles were formed within the EPS. Thus, the mechanism of the biomineralization induced by E. ludwigii SYB1 can be divided into three stages: i) the production of carbonate anhydrase and ammonia increases the alkalinity and saturation state of the mileu, ii) free calcium and magnesium ions are adsorbed and chelated onto EPS, iii) nano-minerals crystallize and grow within the EPS. 17 kinds of amino acid were identified within both biotic MHC and the EPS of SYB1, while the percentages of glutamic and aspartic acid in MHC increased significantly (p<0.05). Further, the adsorption energy was calculated for various amino acids on 7 diffracted crystal faces, with preferential adsorption demonstrated on (111) and (222) faces. At the same time, the lowest adsorption energy was always that of glutamic and aspartic acid for the same crystal plane. These results suggest that aspartic acid and glutamic acid always mix preferentially in the crystal lattice of MHC, and that differential adsorption of amino acids on crystal planes can lead to their preferred orientation. Moreover, the mixing of amino acids in the mineral structure may also have a certain influence on the mineral lattice dislocations, so enhancing the thermodynamic characteristics.